Literature review: visible light communication system business model scheme for telecommunication business in Indonesia - Wicaksono, Khalfan Nadhief Prayoga; Apriono, Catur (Matrix : Jurnal Manajemen Teknologi dan Informatika, 2023)
The telecommunication sector mainly comprises operators, vendors, and regulators. In Indonesia, tele- communications operator companies tend to decrease profits from the first quarter of 2017 to the third quarter of 2018. This condition is due to the tight competition of telecommunication service providers, high operational costs, and digital transformation that does not provide substantial revenue for the company. Telecommunica- tions operators need other service options that can expand target market segmentation. It aims to open up a new blue ocean as a new source of income. The world is getting closer to massive communication technology, so high-speed communication is needed. Therefore, telecommunications operators can open new service options based on the visible light spectrum as their communication resources. This option can be integrated with ambient lighting, a wide spectrum ranging from radio waves, and greater bandwidth, making visible light suitable for IoT- 5G services. This research aims to design a wireless visible light communication business model. Several frame- works are used, such as the magic triangle of St. Gallen, Osterwalder Business Model Canvas, and PESTLE analysis. The business model design results in a business model with B2B market segmentation being the main focus and B2C market segmentation to acquire retail customers.